An agent-based model to simulate SARS-CoV-2 contamination of surfaces and meat cuts in processing plants - Ngoc-Du Martin Luong; Laurent Guillier; Michel Federighi; Yvonnick Guillois; Pauline Kooh; Anne-Laure Maillard; Mathilde Pivette; Géraldine Boué; Sandra Martin-Latil; Estelle Chaix; Steven Duret (International Journal of Food Microbiology, 2023)

Identification of Workers at Increased Risk of Infection During a COVID-19 Outbreak in a Meat Processing Plant, France, May 2020 - Yoann Mallet; Mathilde Pivette; Matthieu Revest; Elisabeth Angot; Marion Valence; Clarisse Dupin; Nicolas Picard; Guillaume Brelivet; Thomas Seyler; Stéphany Ballet; Alain Le Tertre; Yvonnick Guillois (Food and Environmental Virology, 2021)
On 13 May 2020, a COVID-19 cluster was detected in a French processing plant. Infected workers were described. The associations between the SARS-CoV-2 infection and the socio-demographic and occupational characteristics were assessed in order to implement risk management measures targeting workers at increased risk of contamination. Workers were tested by RT-PCR from samples taken during screening campaigns. Workers who tested positive were isolated and their contacts were quarantined. Workers were described and associations with the SARS-CoV-2 infection were assessed through risk ratios using multivariable Poisson regression. Of the 1347 workers, 87.5% were tested: 140 cases were identified; 4 were hospitalised, including 2 admitted to intensive care. In the company, the cluster remained limited to deboning and cutting activities. The attack rate was 11.9% in the company, reaching 16.6% in the cutting department. Being an employee of a subcontractor significantly increased the risk of infection by 2.98 [1.81–4.99]. In the cutting department, an association with virus infection was found for a group of non-French speaking workers from the same Eastern European country (RR = 2.67 [1.76–4.05]). They shared accommodation or carpooled more frequently than the other cases. The outbreak investigation revealed a significantly increased risk of SARS-CoV-2 infection for workers of subcontractors and some foreign-born workers. There are many such populations in meat processing plants; the observed associations and the ways in which these workers are contaminated need to be confirmed by further work. Prevention campaigns should now target these workers. Environmental risk factors in the workplace setting remain to be clarified.